Insulin potentiating activity of cinnamomum extract on 3T3-L1 adipocytes - M., Taher; Abdul Majid, Fadzilah Adibah; Sarmidi, Mohamad Roji (Universiti Malaysia Sabah, 2003)
Non-insulin dependent diabetes melitus (NIDDM), or Type II diabetes is one of the largest health problems in the world. Several plant phytochemicals can directly stimulate insulin secretion and/or action. In this work, the activity of chalcone polymer isolated from Cinnamomum zeylanicum on 3T3-L1 adipocytes was investigated. The compound was isolated using silica gel column chromatography. The result shows that at a dose of 100Î¼g/mL, the compound gave the higher action than insulin alone by increasing glucose consumption 3 hours after simulation. When the compound was combined with insulin (100nM), the glucose consumption increased about 25%. In contrast when the compound was administered on preconfluent 3T3-L1 preadipocytes, there was no significant effect. Cell proliferation also increased after addition of the compound. Cell proliferation was detected by MTT assay. Based on the experimental data it can be shown that the compound promote glucose metabolism and subsequently enhanced cell growth. The type of action of the compound was synergic effect to insulin activity.